Divine Traces in Code: Algorithmic Analysis of the Order Patterns of the Universe from an Islamic Perspective - Kurniawan, Ade Fakih; Wahyudi, M Iman; Megandani, Adi (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This article examines the relationship between Islamic theological conceptions of cosmic order and contemporary discussions of algorithmic structure in computational science. The study focuses on proposing a conceptual and interpretive framework for understanding recurring patterns in nature—such as mathematical regularities, systemic interdependence, and structural coherence—through the lens of Islamic cosmology. This approach moves beyond a simple empirical demonstration of divine design. By synthesizing scientific literature on pattern formation with Islamic intellectual traditions, this paper argues that computational models can serve as heuristic tools for interpreting natural order within a theistic worldview. Consequently, the claims are situated within a theological–philosophical discourse that reflects on how structured regularities may be meaningfully interpreted as signs (āyāt) of divine wisdom, rather than being framed as empirical proof of divine agency. In doing so, the study contributes to interdisciplinary conversations on religion, science, and digital epistemology, offering a nuanced account of how faith-based cosmology can critically engage contemporary computational paradigms.